Heavy Metal Remediation from Contaminated Soil Using Biochars and Modified Biochars: A Review - Asha Siddika; Zakia Parveen (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
From the beginning of the industrial revolution, metal refining industries using the pyrometallurgical process are generating remarkable emissions of heavy metals. As the main objective of these pollutants, a great number of soils are now contaminated over extensive areas depending on exposure level, and duration, and pose a major risk to human health worldwide. Biochar, a co-product of the pyrolysis process, can be used to nourish soil health, and remediate heavy metals. They are nowadays modified to enhance the sorption capacity of biochar and immobilization of heavy metals. Immobilization, as an in-situ application method, is a cost-effective method for environmental remediation of heavy metals in the soils. The research statistics on biochar and modified biochar influences on heavy metal remediation from the soil are scarce. Therefore, the purposes of this review are (1) to combine modification processes of biochar (2) to offer possible mechanisms associated with the reduction of heavy metals (iii) to combine the available data on the positive effects of biochars and modified biochars on heavy metal remediation(iv) identify researchable priorities.